Social science perspectives on drivers of and responses to global climate change. (9th September 2018) - Jorgenson, Andrew K.; Fiske, Shirley; Hubacek, Klaus; Li, Jia; McGovern, Tom; Rick, Torben; Schor, Juliet B.; Solecki, William; York, Richard; Zycherman, Ariela
Abstract : This article provides a review of recent anthropological, archeological, geographical, and sociological research on anthropogenic drivers of climate change, with a particular focus on drivers of carbon emissions, mitigation and adaptation. The four disciplines emphasize cultural, economic, geographic, historical, political, and social‐structural factors to be important drivers of and responses to climate change. Each of these disciplines has unique perspectives and makes noteworthy contributions to our shared understanding of anthropogenic drivers, but they also complement one another and contribute to integrated, multidisciplinary frameworks. The article begins with discussions of research on temporal dimensions of human drivers of carbon emissions, highlighting interactions between long‐term and near‐term drivers. Next, descriptions of the disciplines' contributions to the understanding of mitigation and adaptation are provided. It concludes with a summary of key lessons offered by the four disciplines as well as suggestions for future research. This article is categorized under: Climate Economics > Economics and Climate Change Abstract : This article provides a review of recent anthropological, archeological, geographical, and sociological perspectives on anthropogenic drivers of climate change, with a particular focus on drivers of carbon emissions, mitigation and adaptation.